2023
DOI: 10.1007/s10765-023-03242-x
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Soret and Thermodiffusion Coefficients in Binary and Ternary Liquid Mixtures

Abstract: This review provides an overview of the major, currently used techniques for investigating the Soret effect and measuring thermodiffusion and Soret coefficients, and in most cases also isothermal Fickian diffusion coefficients, in liquid mixtures. The methods are introduced with a focus on binary mixtures. The optical methods comprise optical beam deflection (OBD), optical digital interferometry (ODI) both on the ground and under microgravity conditions in the SODI-IVIDIL experiment for the study of the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…As a result, the Soret effect reduces the wall superheat by accumulating the component with the higher partial pressure near the surface. This ensures a continuous liquid supply to the nucleation sites, preventing dry-out and maintaining the efficient replenishment of the liquid phase. ,, It is suggested that varying the magnetic field strength could be a viable method to fine-tune the nickel alignment morphology and optimize performance further. Further investigations are warranted to explore and fine-tune the alignment morphologies of the Cu/Ni surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the Soret effect reduces the wall superheat by accumulating the component with the higher partial pressure near the surface. This ensures a continuous liquid supply to the nucleation sites, preventing dry-out and maintaining the efficient replenishment of the liquid phase. ,, It is suggested that varying the magnetic field strength could be a viable method to fine-tune the nickel alignment morphology and optimize performance further. Further investigations are warranted to explore and fine-tune the alignment morphologies of the Cu/Ni surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the Soret and Marangoni effects arising from the surface tension and concentration gradients within the binary mixture also contribute to the improved boiling performance. The Soret effect, or thermal diffusion, causes a separation of the mixture components in response to a temperature gradient. , The Marangoni effect, on the other hand, induces fluid motion along the interface due to a surface tension gradient. This effect can cause the vapor bubbles in the binary mixture to shift toward the high-temperature area, further promoting liquid replenishment at the nucleation sites and preventing dry-out. , The impact of the Soret and Marangoni effects on heat transfer characteristics has been well-documented for plain surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Further setup specifications and details of the fitting procedure can be found elsewhere. 42 As can be deduced from eqn (4), OBD requires optical properties of the sample, such as the thermal (qn/qT) p,c and solutal contrast factors (qn/qc) p,T . The former quantifies the variation of the refractive index as a function of temperature and is determined using a classical Michelson interferometer.…”
Section: Methodsmentioning
confidence: 99%